Cephalic Tetanus: A Case Report - M. A. Alhaji; U. Abdulhafiz; C. I. Atuanya; F. L. Bukar (Case Reports in Infectious Diseases)
A case report of cephalic tetanus in a 2-year-old girl who was not immunized against tetanus following suppurative otitis media (SOM) is presented. This case is reported because of the rarity of cephalic tetanus associated with high mortality, to highlight the risk of cephalic tetanus as sequelae of SOM and the need for proper aural care and prompt treatment of SOM. Primary immunization of all eligible children as well as booster vaccination at appropriate time as an effective management strategy for tetanus is emphasized.